Arboreal diversity in dairy-producing properties in the Arroio da Seca micro-river basin, Rio Grande do Sul, Brazil - Zerwes, Cristian Mateus; Rempel, Claudete; Morás, Ana Paula de Borba (Ciência e Natura, 2022)
The Deciduous Seasonal Forest (DSF) in Rio Grande do Sul (RS) is fragmented and partially protected by environmental legislation [Legal Reservation (LR) and Permanent Preservation Area (PPA)]. The aim of this study was to characterize diversity of the arboreal species situated in LR and PPA of 12 dairy-producing properties in the Arroio da Seca micro-river basin. A total of 398 plots with 100m² were used, and height, perimeter, and species were recorded. Phytosociological parameters were calculated using an electronic spreadsheet. Richness of 130 species was recorded as well as a Shannon-Wiener index of 3.79 (0.04). Ninety percent of the sampled area is in the early and intermediate stages of regeneration and most species with high importance value are typical of secondary vegetation. The PPA had higher estimated richness and diversity than the LR; however, there was higher infestation of exotic species in the PPA.